Conflicts of red partisans and Eastern Lithuania armed self defence troups in 1943 - Zizas, Rimantas (Genocidas ir rezistencija, 2004)
This article presents the history of the armed local self–defence units formed by the Soviet partisans and the armed local self–defence units formed with the permission of the German occupation authorities. Dargužiai was undoubtedly among the first villages in south–eastern Lithuania that tried to arm themselves and resist the red partisans.
Keywords: German occupation; Soviet partisans; resistance; Eastern Lithuania